Pengaruh Bauran Pemasaran Terhadap Keputusan Pembelian Di Toko Reyshop Sangatta - Hasmah (Jurnal Ilmiah Raflesia Akuntansi, 2025)
This study was conducted with the aim of determining the influence of marketing mix on purchasing decisions, with the determination of the number of samples based on the Lemeshow formula, which was 96 respondents. To obtain data in this study, the author used questionnaire data techniques or online questionnaires through google forms. The sampling technique used is probability sampling with incidental sampling method. The data analysis technique is quantitative with simple linear regression analysis. The conclusion of this study is that the marketing mix affects purchasing decisions at the Reyshop Sangatta Store.